LEXICAL DENSITY AND GRAMMATICAL INTRICACY IN DEBATERS’ SPEECHES - Putry Amelia; Tengku Silvana Sinar; Tengku Thyrhaya Zein (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2020)
This paper entitled “Lexical Density and Grammatical Intricacy in Debaters’ speeches (Case Study of National University Debating Championship 2018)” discusses the lexical density and grammatical intricacy to identify the level of lexical density and grammatical intricacy in debaters’ speeches conducted by means of descriptive qualitative method. The theories supporting this thesis are the ones proposed by Ure, Halliday, and Simon Quinn. The data source in this thesis were debate speech from Main Grand Final round of NUDC 2018 which are Opening Government team (Prime Minfister and Deputy Prime Minister) and Opening Opposition team (Leader of the Opposition and Deputy Leader of the Opposition) taken from youtube video of NUDC 2018, Malang. The data in this study were lexical items for lexical density and clauses for grammatical intricacy. The step passed in this analysis are collecting the data by transcribing the debate speech into text, identifying the lexical items and clauses, and concluding the analysis. The result of this thesis shows that lexical density and grammatical intricacy of Prime Minister = 40.95 % and 3.43, Deputy Prime Minister = 42.44% and 2.72, Leader of the Opposition = 46.14% and 2.91, and Deputy Leader of the Opposition = 47.90% and 3. Thus, both the level of lexical density and grammatical intricacy in debaters’ speeches account for higher density and intricacy, so debaters’ speeches represent much information due to many lexical items as the proportion of running words and indicate that clause complex is more dominant than simple sentence.